Hydroxychloroquine Toxicity in the Vital Organs of the Body: In Vivo Study - Alruwaili, Meshref; Jarrar, Bashir; Jarrar, Qais; Alruwaili, Majed; Goh, Khang Wen; Moshawih, Said; Ardianto, Chrismawan; Long, Chiau Ming * (IMR Press, 2023)
Background: Hydroxychloroquine (HCQ) toxicity can adversely affect vital organs, cause pathologic ocular damage, and can have direct cardiovascular effects. This study aims to identify the biochemical, hematological, and histological alterations of the vital organs associated with the effects of HCQ.